Inclusive Education in Ghana: Differing Perceptions among Teachers. - Butakor, P.K.; Boateng, F. (My University, 2017)
Social and inclusive education as captured under the Sustainable Development Goals (SDGs) has enjoined most countries to implement policies to bring about education for all. Inclusive education recognizes that learners come from diverse backgrounds with varied characteristics, which include different learning capacities and cognitive development. And that incorporating all categories of people into the mainstream educational facilities is a way to build inclusive societies. Though there have been several improvements in education in Ghana as a result of policies implemented by previous and current governments, the education system still has some challenges when it comes to inclusion. These challenges include the public prejudiced perception of persons with special needs, architectural barriers, inadequate assessment facilities, inaccessible curriculum, curriculum inflexibility and pre-/post-training in special education needs for regular teachers. The purpose of this study was to examine Ghanaian teachers’ perception towards inclusive education. The Multidimensional Attitudes Toward Inclusive Education Scale (MATIES) developed by Mahat (2008) was administered to 280 randomly selected teachers within Accra. The MATIES is an 18-item scale scored on six points Likert scale ranging from strongly disagree, disagree, somewhat disagree, somewhat agree, agree, and strongly agree, and comprised of three dimensions: cognitive, affective, and behavioural domains; each measured by six indicators or items. The results of Confirmatory Factor Analysis (CFA) yielded estimates with poor fit indices (CFI = 0.780; TLI = 0.745; RMSEA = 0.125; and SRMR = 0.150) in comparison with the acceptable fit indices. This clearly showed that the three-factor structure of the MATIES theorized by Mahat (2008) was not supported by the Ghanaian sample. A follow-up Principal Axis Factoring with an Oblimin with Kaizer Normalization rotation yielded a four-factor structure for the MATIES with the Ghanaian sample. These four factors were labelled; Behavioural, Affective, Positive Beliefs, and Negative Beliefs. The reliability coefficients for these four subscles were 0.90. 0.86, 0.77, and 0.73 respectively. Results of independent t-test indicated a significant statistical difference between males and females on their negative beliefs towards inclusive education, t (273) = 3.516, p-value = 0.001., where men (Mean = 7.628, SD = 3.194) exhibited more negative beliefs towards inclusive education than females (Mean = 6.384, SD = 2.595). For differences across the categories of highest educational qualification (certificate A, Diploma in Basic Education, Higher National Diploma, Bachelors, and Masters), ANOVA results indicated a statistically significant difference on the behavioural subscale, F(5,278) = 4.178, p=0.001. A post hoc Tukey test revealed that the difference was between certificate “A” teachers against the remaining categories. The post hoc test also showed a difference between teachers with bachelors and those with master’s degrees. ANOVA results also indicated differences across teaching experience on the affective dimension of the MATIES, F (3,276) = 5.059, p=0.001. A post hoc Tukey test identified a significant difference between teachers with less than 3 years teaching experience and those who have taught between 3 – 10 years. Significant differences were also noted between 3 – 10 and the 20+ years of teaching experience groups. Finally the ANOVA results didn’t find any statistically significant difference between the ages of teachers, the level they teach and the four dimensions of teachers’ attitudes towards inclusive education. Implications of these findings will be discussed.
Seminar
Keywords: Inclusive education; teachers; perception; Ghana